Pengaruh Pemberian Trancutaneus Electrical Nerve Stimulation (Tens) Dan Mc. Kenzi Exercise Terhadap Penurunan Nyeri Pada Penderita Ischialgia Di Poli Fisioterapi Rsud Meuraxa Banda Aceh - Siti Hajar; Mustafa Al Haris; Yeni Vera (LPPM STIKES Siti Hajar dan Insight Power, 2023)
Background: Ischialgia is a debilitating condition in which the patient experiences pain and paresthesias in the distribution of the sciatic nerve or associated lumbosacral nerve roots. Ischialgia is pain as a direct result of sciatic nerve pathology. The sciatic nerve innervates direct motor function in the hamstring muscles, the adductor of the lower extremity, and indirect motor function in the calf muscles, forelimb muscles, and some intrinsic muscles of the foot. Ischialgia often occurs when this multifunctional nerve is compressed in the lumbar region, usually due to herniation of the disc from the spine. Methods: The design of this study is a quantitative study with a quasi-experimental research design with a pre and post test approach. This quasi-experimental study was intended to describe changes in pain reduction. Sampling was carried out by the total sampling method, namely the entire population obtained was used as a research sample of 21 patients suffering from ischialgia. The research instrument used by the researcher is the Visual Analog Scale (VAS) with a value of 0-10. Results: The normality test used is Saphiro Wilk and statistical test using Wilcoxon with p = 0.000 (p <0.05) then H0 is rejected and H1 is accepted and concluded that there is an effect of giving Transcutaneous Electrical Nerve Stimulation (TENS) and Mc. Kenzi Exercisercise to reduce pain in patients with Ischialgia. Conclusion: based on the analysis, it is known that there are differences in the effect of pretest and posttest giving Transcutaneous Electrical Nerve Stimulation (TENS) and Mc. Kenzi Exercisercise to reduce pain in patients with Ischialgia. Keywords: TENS, Mc. Kenzi Exercisercise, Pain, Ischialgia